High-voltage cable material capable of resisting 105 DEG C, cable and preparation method
By introducing modified nanoinorganic powders and dispersed modified epoxy resins and polyarylene sulfide resins into low-density polyethylene, a nanointerface is formed to inhibit charge aggregation and thermal movement, the problem of insufficient stability and safety of existing crosslinked polyethylene insulating materials in high-voltage and high-temperature environments is solved, and the high-voltage and high-temperature resistance of cable materials is significantly improved.
Patent Information
- Application Number
- CN202510317261.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-18
AI Technical Summary
Existing crosslinked polyethylene (XLPE) insulating materials are difficult to meet the stability and safety requirements for long-term use in high-pressure and high-temperature environments, especially in high-temperature environments such as aerospace and shipbuilding.
By introducing modified nanoinorganic powders into low-density polyethylene, combined with dispersion modification technology of epoxy resin and polyarylene sulfide resin, a nanointerface is formed to suppress charge aggregation and thermal movement, and to improve the high voltage and high temperature resistance of cable materials.
It significantly improves the breakdown field strength and heat resistance of cross-linked polyethylene cable materials, extends the service life of the cable, and maintains stability at higher temperatures (to 105°C), meeting a wider application needs.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer cable materials, and in particular to a high-voltage cable material and a cable capable of withstanding 105° C., and a preparation method thereof. Background Art
[0002] As an important technical symbol of the current power grid, high-voltage transmission technology has put forward extremely high requirements for the industry. With the gradual increase in transmission voltage levels, the requirements for the voltage resistance and temperature resistance of cable materials are getting higher and higher. At present, it is urgently needed to solve the stability and effectiveness of cable materials under high voltage and high temperature through cross-industry solutions.
[0003] Cross-linked polyethylene (XLPE) has become the mainstream insulation material for high-voltage cables due to its good electrical properties, high insulation resistance, low dielectric loss tangent, high breakdown strength and other characteristics. It can withstand large currents, high voltages, strong electromagnetic fields, etc. According to the mature technology of cross-linked polyethylene (XLPE) insulation cable materials, the long-term maximum allowable temperature level of cross-linked polyethylene cables is set at 90°C, which is based on the comprehensive consideration of the thermal stability, mechanical properties and cable design of its materials. The maximum temperature of the cable in a short-term overload shall not exceed 130°C; the maximum temperature of the cable in a short-circuit shall not exceed 250°C, and the duration shall not exceed 5 seconds. These technical standards ensure that the cable can operate safely and reliably under normal working conditions.
[0004] However, as the cable is used for a longer time, cross-linked polyethylene (XLPE) insulation materials often experience thermal aging. The small groups generated by thermal aging will further ionize under the action of the electric field, especially in high-voltage cables, which can easily cause rapid accumulation of charges inside the insulation material. The accumulation of space charges inside the insulation material will accelerate the aging of the insulation layer, eventually leading to failure of the cable insulation layer and inability to operate stably and safely. Obviously, for some high-temperature operating environments such as aerospace, shipbuilding, military industry, boilers, refineries, metallurgical plants, fertilizer plants, and glass plants, the temperature resistance level of existing cross-linked polyethylene (XLPE) insulation materials is even more difficult to meet the requirements. If the temperature resistance level of cross-linked polyethylene (XLPE) insulation materials is increased to 125°C, it can not only increase the service life and safety stability of the cable, but also allow cables with cross-linked polyethylene (XLPE) as insulation materials to be used in a wider range.
[0005] The long-term allowable operating temperature of the existing cross-linked polyethylene (XLPE) insulating material is 90°C, and the conductivity of cross-linked polyethylene will change significantly with the accumulation of charge and temperature gradient, affecting the performance of the insulating material. Technicians control the cleanliness of cross-linked polyethylene to reduce impurities and maximize the characteristics of the material itself. The long-term temperature resistance of the material is determined by the characteristics of the polyethylene material. It is difficult to achieve long-term tolerance of 105°C, and polyethylene needs to be modified. According to the disclosed technology, inorganic nanoparticles have been used to improve the dielectric properties and temperature resistance of polyethylene, but the dispersion performance of nanoparticles is limited, and it is difficult to achieve the designed effect. In particular, when a single nanoparticle is dispersed, it is very easy to agglomerate, which will cause a decrease in dielectric properties. There are also functional groups modified polyethylene by grafting modification to improve high pressure resistance and high temperature resistance. However, the high temperature resistance is not ideal.
[0006] In order to adapt to the continuous improvement of power grid voltage levels, ensure the insulation of cables at higher temperatures, and ensure the stability, reliability and safety of power grid operation, the present invention proposes a cable material that can withstand a temperature of 105°C. Summary of the invention
[0007] In order to improve the high voltage resistance and long-term high temperature stability of cross-linked polyethylene used as cable material, the present invention discloses a high voltage cable material that can withstand 105°C, aiming to further improve the long-term temperature tolerance level of the cross-linked polyethylene cable material and ensure the service life and safe operation of the cable.
[0008] The technical solution of the present invention is as follows:
[0009] According to one aspect of the present invention, a high-voltage cable material capable of withstanding 105°C is provided, characterized in that the material comprises the following raw materials by weight: 85-90 parts of low-density polyethylene, 8-10 parts of modified nano-inorganic powder, 0.5-0.8 parts of maleic anhydride, 1.5-2.5 parts of a cross-linking agent, 0.2-0.5 parts of a co-cross-linking agent, and 0.3-0.5 parts of an antioxidant; wherein the modified nano-inorganic powder is a nano-inorganic powder modified by epoxy resin combined with polyarylene sulfide resin under the dispersion effect of styrene maleic anhydride copolymer.
[0010] Preferably, the modified nano inorganic powder is obtained by grinding and dispersing nano inorganic powder, epoxy resin, polyarylene sulfide resin, and styrene maleic anhydride copolymer at a mass ratio of 100:20-30:20-25:0.2-0.3. The modified nano inorganic powder is introduced into low-density polyethylene, and the modified nano inorganic powder is evenly dispersed in the low-density polyethylene, which inhibits charge accumulation, hinders the thermal motion of polymer chain segments, reduces the possibility of thermal decomposition, and significantly improves the breakdown field strength and heat resistance of the cable material.
[0011] Styrene maleic anhydride copolymer (SMA) is a polymer material synthesized by copolymerization of styrene and maleic anhydride. It has good thermal stability and can effectively depolymerize and disperse nano inorganic powders.
[0012] Preferably, the polyarylene sulfide resin is at least one of powdered polyphenylene sulfide (PPS) and polyarylene sulfide sulfone (PASS). Polyarylene sulfide resin is a type of high molecular polymer with a main chain structure of sulfur and aromatic structure alternately connected, which has good high temperature resistance. Polyarylene sulfide resin is usually in fine powder form and is easy to grind into fine powder. By grinding with epoxy resin and nano inorganic powder, the nano inorganic powder is dispersed and modified under the dispersion effect of styrene maleic anhydride copolymer, thereby promoting dispersion in low density polyethylene. At the same time, the interface of polyarylene sulfide resin and epoxy resin dispersed in low density polyethylene is increased, which is significant for improving the high temperature resistance of cross-linked polyethylene.
[0013] It is particularly preferred that the melt index of the polyarylene sulfide resin is greater than 200g / 10min. Polyarylene sulfide resins are generally high melt index resins, and the melt index of the existing popular polyarylene sulfide resins can even reach 1200-2000g / 10min; polyarylene sulfide resins are dispersed in low-density polyethylene, and in the cross-linking process at a high temperature of 280-320°C, the cross-linking agent decomposition products cause micropores in the insulating material, and at this temperature, the polyarylene sulfide resin dispersed in the low-density polyethylene begins to melt and flow, filling the micropores generated by the cross-linking of the low-density polyethylene, which can reduce the accumulation of space charges during high-voltage transmission, and at the same time form a high-temperature resistant interface, thereby improving the breakdown field strength and temperature resistance of the cross-linked polyethylene.
[0014] Preferably, the epoxy resin is selected from epoxy resins with an epoxy value of 0.1-0.6 eq / 100g. Bisphenol A epoxy resin is particularly preferred, which basically does not produce small molecule volatiles during curing and has high toughness and heat resistance after curing. The epoxy resin is dispersed in low-density polyethylene, and in the high-temperature cross-linking stage, the epoxy resin is thermally cured to enhance the breakdown field strength and temperature resistance of the cross-linked polyethylene.
[0015] Further preferably, the nano inorganic powder is selected from at least one of MgO, ZnO, Al2O3, and SiO2. In particular, the nano inorganic powder is selected to have a nano size of 20-50nm, and the nano inorganic powder of this size takes into account both dispersibility and excellent electrical properties. The nano inorganic powder is uniformly doped with low-density polyethylene after modification, and has excellent breakdown field strength.
[0016] According to the present invention, nano inorganic powders are modified by combining epoxy resin and polyarylene sulfide resin. On the one hand, nano inorganic powders are efficiently dispersed in low density polyethylene, nano interface is established to inhibit charge accumulation, and heat resistance is improved. On the other hand, the dispersion of epoxy resin and polyarylene sulfide resin is promoted. When cross-linked at high temperature, epoxy resin is solidified to form a high pressure and high temperature resistant interface, and polyarylene sulfide resin is melted and flows in situ, filling micropores generated by decomposition of cross-linking agent, thereby significantly improving breakdown field strength and high temperature resistance of cross-linked polyethylene.
[0017] Maleic anhydride is grafted onto low-density polyethylene under thermal conditions. The introduced polar groups can prevent the orderly migration of ionized charges under the action of the electric field, inhibit the formation of space charges, and significantly improve the breakdown field strength of cross-linked polyethylene.
[0018] Preferably, the antioxidant is a thiobisphenol antioxidant. A thiobisphenol antioxidant can significantly improve the thermal stability of cross-linked polyethylene without damaging the dielectric strength. Typically, 4,4'-thiobis(6-tert-butyl-3-methylphenol) can be used.
[0019] Preferably, the antioxidant is a combination of a hindered phenol antioxidant and a thioester antioxidant. Further preferably, the antioxidant is a combination of a hindered phenol antioxidant and a thioester antioxidant in a mass ratio of 2-3:1. Hindered phenol antioxidants have good thermal stability and processing stability, and effectively prevent long-term thermal oxidation degradation of materials; typically, 1076 antioxidants can be used in combination with DSTP.
[0020] Preferably, the cross-linking agent is at least one of dicumyl peroxide (DCP) and benzoyl peroxide (BPO).
[0021] Preferably, the auxiliary cross-linking agent is at least one of diallyl phthalate, triallyl cyanurate, and 1,2-polybutadiene.
[0022] According to another aspect of the present invention, a method for preparing the above-mentioned high-voltage cable material capable of withstanding 105° C. is provided, wherein the specific preparation method is as follows:
[0023] (1) weighing nano-inorganic powder, epoxy resin, polyarylene sulfide resin, and styrene maleic anhydride copolymer according to a mass ratio of 100:20-30:20-25:0.2-0.3, adding the mixture into a closed grinder for grinding and modification, and obtaining modified nano-inorganic powder;
[0024] (2) 85-90 parts of low-density polyethylene, 8-10 parts of modified nano-inorganic powder, 0.5-0.8 parts of maleic anhydride, 1.5-2.5 parts of cross-linking agent, 0.2-0.5 parts of auxiliary cross-linking agent and 0.3-0.5 parts of antioxidant are mixed by automatic weight loss weighing according to weight parts, dispersed and mixed at high speed in a high-speed mixer for 30-60 minutes, and extruded through a twin-screw extruder with the screw temperature set at 110-120°C. After hot-melt extrusion, conveying by chain conveyor belt, air cooling and pelletizing, a high-voltage cable material that can withstand 105°C is obtained.
[0025] The 125° C. resistant high-voltage cable material is used for the insulation layer of the high-voltage cable and needs to be cross-linked at 280-320° C. under nitrogen protection, so that the insulation layer can meet the temperature grade of 105° C. for long-term operation.
[0026] Preferably, the closed grinding mill in step (1) is determined according to the form of the material to be ground. When the epoxy resin is a brittle solid, a dry powder ball mill or a jet mill is used for grinding and dispersion; when the epoxy resin is a liquid, a colloid mill or a three-roll grinder is used for grinding.
[0027] Preferably, the twin-screw extruder in step (2) is a low aspect ratio co-rotating twin-screw extruder with a screw aspect ratio of 25 / 1-30 / 1. It has a lower shear rate to prevent overheating and premature cross-linking of the material.
[0028] In addition, the present invention also provides a cable, which is characterized in that a high-voltage cable material that can withstand 105°C is used as the insulation layer.
[0029] Furthermore, the present invention also provides a method for preparing the cable, which is characterized in that an inner shielding layer, an insulating layer, and an outer shielding layer are sequentially extruded on a conductor core by three-layer co-extrusion; after the extrusion is completed, a cross-linking treatment is carried out through a high-temperature nitrogen pipeline at a pressure of 1.0-1.2MPa and 280-320°C for 8-10min to obtain a cable core; an alloy lead sheath is wrapped around the cable core, and a sheath is extruded and coated to obtain a cable.
[0030] Preferably, the inner shielding layer and the outer shielding layer in the cable preparation method are made of conventional shielding materials in the art or homemade shielding materials.
[0031] Preferably, the three-layer co-extruders described in the preparation method of the cable are extruders for the inner shielding layer, the insulating layer, and the outer shielding layer, respectively, and are equipped with 65-type, 150-type, and 90-type single-screw extruders according to the extrusion volume; the processing temperature set for the extrusion of the inner and outer shielding layers is 100-110°C; the processing temperature set for the extrusion of the insulating layer is: 90°C for the first section, 100°C for the second section, 105°C for the third section, 105°C for the fourth section, 110°C for the fifth section, 110°C for the sixth section, 110°C for the seventh section, 115°C for the eighth section, 115°C for the ninth section, and 118°C for the tenth section. The 150-type extruder for extruding the insulating layer is equipped with a vacuum exhaust port, and the vacuum degree is set to 0.06-0.08MPa, and the volatiles that affect the density of the insulating layer are promptly removed through the vacuum exhaust port.
[0032] The invention provides a high-voltage cable material, a cable and a preparation method capable of withstanding 105°C. The invention has the following effects:
[0033] 1. The present invention uses epoxy resin and polyarylene sulfide resin to disperse and modify nano inorganic powder under the dispersing effect of styrene maleic anhydride copolymer, thereby promoting the effective dispersion of nano particles, uniformly doping low-density polyethylene with nano-sized particles, and improving the breakdown field strength and heat resistance of the material.
[0034] 2. The present invention disperses epoxy resin and polyarylene sulfide resin in low-density polyethylene. During high-temperature cross-linking, the epoxy resin solidifies and the polyarylene sulfide resin melts and flows, filling the micropores generated by the decomposition of the cross-linking agent and forming a high-temperature and high-pressure resistant interface, thereby significantly improving the breakdown field strength and high-temperature resistance of the cross-linked polyethylene.
[0035] 3. The present invention can prevent the orderly migration of ionized charges, inhibit the formation of space charges, and significantly improve the breakdown field strength of cross-linked polyethylene by introducing maleic anhydride to graft polyethylene.
[0036] 4. The cable material of the present invention improves the stability of the cable in a high temperature environment, prolongs the service life of the cable, and ensures the reliable operation of the cable. The manufacturing process is easy to control, has no special requirements for production equipment, and can be directly mass-produced without modifying the existing production line. DETAILED DESCRIPTION
[0037] In order to enable those skilled in the art to further understand the technical means, technical objectives and technical effects achieved by the present invention, the present invention is described in detail below with reference to embodiments.
[0038] Some basic raw materials used in the implementation plan:
[0039] Low-density polyethylene: Model 2426H, melt index is 2g / 10min (200℃, 5kg load), produced by Huizhou CNOOC Shell.
[0040] Polyphenylene sulfide: Model 1130C, white powder, melt index is 250g / 10min (316℃, 5kg), produced by Zhejiang Xinhecheng Co., Ltd.
[0041] Styrene maleic anhydride copolymer: model BYK-2013, produced by BYK Chemical Company of Germany.
[0042] Example 1
[0043] (1) Nano-Al2O3 (particle size 20-50 nm), epoxy resin E-20, polyphenylene sulfide (1130C), and styrene maleic anhydride copolymer were weighed in a mass ratio of 100:30:25:0.3, added into a closed dry powder ball mill, and ground for 2 h using zirconia ceramic balls as grinding media to obtain modified nano-inorganic powder;
[0044] (2) 85 parts of low-density polyethylene (2426H), 10 parts of modified nano-inorganic powder, 0.5 parts of maleic anhydride, 1.8 parts of DCP cross-linking agent, 0.2 parts of triallyl cyanurate cross-linking agent, 0.3 parts of 1076 antioxidant and 0.1 parts of DSTP antioxidant were mixed by automatic weight loss weighing according to weight parts, and dispersed and mixed at a high speed of 700 r / min for 45 minutes in a high-speed mixer. The mixture was extruded by a co-rotating twin-screw extruder with a screw length-to-diameter ratio of 25 / 1, and the screw temperature was set to set the processing temperature as follows: 110°C for the first section, 110°C for the second section, 115°C for the third section, 115°C for the fourth section, 118°C for the fifth section, 120°C for the sixth section, 110°C for the seventh section, 115°C for the eighth section, 115°C for the ninth section and 118°C for the tenth section. The mixture was subjected to hot-melt extrusion, conveying by a chain conveyor belt, air cooling and pelletizing to obtain a high-voltage cable material that can withstand 105°C.
[0045] Example 2
[0046] (1) Weigh nano-MgO (particle size 20-50 nm), epoxy resin E-12, polyphenylene sulfide (1130C), and styrene maleic anhydride copolymer according to a mass ratio of 100:25:25:0.3, add them into a closed dry powder ball mill, use zirconia ceramic balls as grinding media, and grind for 1 h to obtain modified nano-inorganic powder;
[0047] (2) According to weight parts, 90 parts of low-density polyethylene (2426H), 10 parts of modified nano-inorganic powder, 0.8 parts of maleic anhydride, 2.0 parts of DCP cross-linking agent, 0.5 parts of diallyl phthalate cross-linking agent, 0.3 parts of 1076 antioxidant and 0.1 parts of DSTP antioxidant were mixed by automatic weight loss weighing, and dispersed and mixed at a high speed of 700 r / min for 30 minutes in a high-speed mixer. The mixture was extruded through a co-rotating twin-screw extruder with a screw length-to-diameter ratio of 25 / 1, and the screw temperature was set to set the processing temperature as follows: 110°C for the first section, 110°C for the second section, 115°C for the third section, 115°C for the fourth section, 118°C for the fifth section, 120°C for the sixth section, 110°C for the seventh section, 115°C for the eighth section, 115°C for the ninth section and 118°C for the tenth section. After hot-melt extrusion, strip drawing, chain conveyor belt conveying, air cooling and pelletizing, a high-voltage cable material with a resistance to 105°C was obtained.
[0048] Example 3
[0049] (1) Weigh nano-SiO2 (particle size 20-50 nm), epoxy resin E-44, polyphenylene sulfide (1130C), and styrene maleic anhydride copolymer according to a mass ratio of 100:30:20:0.2, add them into a three-roll mill, and grind for 2 h to obtain modified nano-inorganic powder;
[0050] (2) 85 parts of low-density polyethylene (2426H), 10 parts of modified nano-inorganic powder, 0.8 parts of maleic anhydride, 1.8 parts of DCP crosslinking agent, 0.4 parts of diallyl phthalate crosslinking agent, and 0.4 parts of thiobisphenol antioxidant 4,4'-thiobis(6-tert-butyl-3-methylphenol) were mixed by automatic weight loss weighing and dispersed in a high-speed mixer at 700 r / min for 60 minutes. n, extruded by a co-rotating twin-screw extruder with a screw length-diameter ratio of 25 / 1, the screw temperatures were set to set processing temperatures as follows: one section at 110°C, two sections at 110°C, three sections at 115°C, four sections at 115°C, five sections at 118°C, six sections at 120°C, seven sections at 110°C, eight sections at 115°C, nine sections at 115°C, and ten sections at 118°C; after hot-melt extrusion drawing, chain conveyor belt conveying, air cooling, and pelletizing, a high-voltage cable material that can withstand 105°C was obtained.
[0051] Example 4
[0052] The cable material prepared in Example 1 is used as the insulating layer material; conductive carbon black CB3100, high-density polyethylene, and ethylene-vinyl acetate copolymer are blended and extruded into granules in a mass ratio of 5:60:30 through a single screw extruder to obtain a shielding material; an inner shielding layer, an insulating layer, and an outer shielding layer are sequentially extruded on the conductor core through three-layer co-extrusion; 65-type, 150-type, and 90-type single screw extruders are sequentially equipped according to the extrusion volume; the processing temperature of the insulating layer extrusion is set as follows: 90°C for the first stage, 100°C for the second stage, 105°C for the third stage, 105°C for the fourth stage, The fifth section is 110℃, the sixth section is 110℃, the seventh section is 110℃, the eighth section is 115℃, the ninth section is 115℃, and the tenth section is 118℃; the 150-type extruder for extruding the insulation layer has a vacuum exhaust port between the sixth and seventh sections, and the vacuum degree is set to 0.08MPa, and the volatiles that affect the density of the insulation layer are promptly removed through the vacuum exhaust port; after extrusion, it is cross-linked through a high-temperature nitrogen pipeline at a pressure of 1.0MPa and 320℃ for 10 minutes to obtain the cable core; an alloy lead sheath is wrapped around the cable core, and a PVC sheath is extruded and coated to obtain a cable.
[0053] Comparative Example 1
[0054] The method of Example 1 is implemented, except that no modified nano inorganic powder is added to the cable material.
[0055] Comparative Example 2
[0056] The method of Example 1 is implemented, except that when treating the modified nano inorganic powder, the epoxy resin is completely replaced by polyphenylene sulfide.
[0057] Comparative Example 3
[0058] The method of Example 1 is implemented, except that the polyphenylene sulfide is completely replaced by epoxy resin when treating the modified nano inorganic powder.
[0059] Comparative Example 4
[0060] The method is implemented according to Example 1, except that no maleic anhydride is added to the cable material.
[0061] Comparative Example 5
[0062] (1) Nano-Al2O3 (particle size 20-50 nm) and styrene maleic anhydride copolymer were weighed in a mass ratio of 100:0.3, added into a closed dry powder ball mill, and ground for 2 h using zirconia ceramic balls as grinding media to obtain modified nano-inorganic powder;
[0063] (2) 85 parts of low-density polyethylene (2426H), 6.5 parts of modified nano-inorganic powder, 0.5 parts of maleic anhydride, 1.8 parts of DCP crosslinking agent, 0.2 parts of triallyl cyanurate crosslinking agent, 0.3 parts of 1076 antioxidant, and 0.1 parts of DSTP antioxidant were mixed by automatic weight loss weighing, and the mixture was dispersed and mixed in a high-speed mixer at 700 r / min for 45 minutes. The extruder is extruded by a co-rotating twin-screw extruder with a rod length-diameter ratio of 25 / 1. The screw temperatures are set to the following processing temperatures: one section 110°C, two sections 110°C, three sections 115°C, four sections 115°C, five sections 118°C, six sections 120°C, seven sections 110°C, eight sections 115°C, nine sections 115°C, and ten sections 118°C. After hot-melt extrusion drawing, chain conveyor belt conveying, air cooling, and pelletizing, a high-voltage cable material that can withstand 105°C is obtained.
[0064] In Comparative Example 5, only styrene maleic anhydride copolymer was used for dispersion when treating the nano inorganic powder, and no epoxy resin or polyphenylene sulfide was used.
[0065] Performance evaluation test:
[0066] The cable material samples of each group of tests were cross-linked according to two processes, one was cross-linked at conventional 180°C (labeled as type A specimens); the other was cross-linked at 320°C to simulate nitrogen pipelines (labeled as type B specimens). The breakdown field strength of the test specimens and the aging conditions under high temperature conditions were tested to determine the high pressure and high temperature resistance of the cable material.
[0067] Conventional crosslinking process specimen preparation (Type A specimen): The cable materials of Examples 1-3 and Comparative Examples 1-5 are melt-extruded at 110°C through a Φ20 single-screw extruder, and the hot materials are fed into the mold of a flat-plate vulcanizer, and a pressure of 10 MPa is applied at a constant temperature of 110°C to fix the shape, and the pressure is maintained for 10 min; the pressure is increased and maintained at 15 MPa for 10 min; the mold is quickly taken out and transferred to a high-temperature flat-plate vulcanizer at a temperature of 180°C, and a pressure of 15 MPa is applied to react for 25 min to complete the crosslinking reaction, and the reaction is naturally cooled, and the internal stress is eliminated and the by-products of the crosslinking reaction are removed by thermal degassing in a vacuum oven at 80°C for 48 h to obtain a specimen to be tested.
[0068] Preparation of simulated nitrogen pipeline cross-linking test specimens (Type B test specimens): The cable materials of Examples 1-3 and Comparative Examples 1-5 are melt-extruded at 110°C through a Φ20 single-screw extruder, and the hot materials are fed into the mold of a flat vulcanizer, and a pressure of 10MPa is applied at a constant temperature of 110°C for shaping, and the pressure is maintained for 10 minutes; the pressure is increased and maintained at 15MPa for 10 minutes; the prefabricated samples are transferred to a closed high-temperature device for simulating nitrogen pipeline cross-linking, the nitrogen pressure is filled to 1.0MPa, the temperature is controlled at 320°C, the samples are cross-linked at high temperature in a nitrogen environment for 10 minutes, naturally cooled, and thermally degassed in a vacuum oven at 80°C for 48 hours to eliminate internal stress and remove cross-linking reaction by-products, to obtain test specimens to be tested.
[0069] (1) Breakdown strength test:
[0070] The DC breakdown strength of the test piece was tested in accordance with the international standard IEC 60243. A cylindrical plate electrode was used, with an upper electrode diameter of 25 mm and a lower electrode diameter of 75 mm, and both electrodes had rounded corners. The test piece was a circular specimen with a thickness of 1 mm and a diameter of 100 mm. During the test, the test piece and the electrode were immersed in silicone oil. The temperature was controlled at 100 °C, the voltage was increased at a rate of 1 kV / s, the voltage value at breakdown was read, and the breakdown field strength was obtained according to E=U / d, where U is the voltage at the breakdown of the test piece and d is the thickness of the test piece. Ten samples were measured for each group of samples, and the breakdown data were analyzed using a two-parameter Weibull distribution. The breakdown field strength corresponding to a cumulative failure probability of 63.2% was used as the final data of the breakdown field strength. The test results are shown in Table 1.
[0071] Table 1 Breakdown field strength data table
[0072]
[0073] According to the above test data, when the cable materials of Examples 1-3 are cross-linked conventionally (Type A), the introduced nanoparticles and the high temperature curing of maleic anhydride grafted polyethylene and epoxy resin improve the material breakdown field strength. Moreover, when cross-linked at a high temperature of 320°C in nitrogen (Type B), the polyarylene sulfide resin dispersed in the material melts and fills the micropores generated by cross-linking, and its breakdown field strength is further improved.
[0074] (2) High temperature resistance test:
[0075] The heat resistance stability of cable materials was tested with reference to JB / T10437. Class B specimens simulating cross-linking of nitrogen pipelines were used as test objects. The cable material specimens of Examples 1-3 and Comparative Examples 1-5 were grouped and heat aged at 135°C and 150°C for 168h and 336h, respectively, to test the change rate of tensile strength and elongation at break of the materials; the materials were heat stretched at 200°C and 0.2MPa load for 15min, and the heat elongation was measured; and the high temperature stability was determined by this. The test results are shown in Table 2.
[0076] Table 2 Heat resistance test data
[0077]
[0078] Through testing, after 168 hours (7 days) of continuous heat aging at 135°C, its performance meets the temperature resistance requirements of basic cables. Further, by extending the aging time and increasing the aging temperature to simulate the long-term use of cross-linked polyethylene in a high temperature environment, the change rates of tensile strength and elongation at break are both within 20%, and the load thermal elongation is within 100%. It is evaluated that its heat aging performance fully meets the long-term tolerance of 105°C grade temperature requirements. It even meets the 125°C grade temperature requirements.
[0079] The detailed technical scheme of the present invention has been described in the above embodiments, and it should be clear that the technician can make modifications and variations without departing from the spirit or scope of the present invention. Therefore, it should be understood that the foregoing is for illustrating the present invention and should not be construed as limiting.
Claims
1. A high voltage cable material capable of withstanding 105°C, characterized in that: The invention comprises the following raw materials by weight: 85-90 parts of low-density polyethylene, 8-10 parts of modified nano-inorganic powder, 0.5-0.8 parts of maleic anhydride, 1.5-2.5 parts of cross-linking agent, 0.2-0.5 parts of auxiliary cross-linking agent and 0.3-0.5 parts of antioxidant; wherein the modified nano-inorganic powder is a nano-inorganic powder modified by epoxy resin combined with polyarylene sulfide resin under the dispersing action of styrene maleic anhydride copolymer.
2. A high voltage cable material capable of withstanding 105°C according to claim 1, characterized in that: The modified nano inorganic powder is obtained by grinding, dispersing and modifying nano inorganic powder, epoxy resin, polyarylene sulfide resin and styrene maleic anhydride copolymer in a mass ratio of 100:20-30:20-25:0.2-0.
3.
3. The high voltage cable material capable of withstanding 105°C according to claim 1, characterized in that: The polyarylene sulfide resin is at least one of powdered polyphenylene sulfide and polyarylene sulfide sulfone.
4. The high voltage cable material capable of withstanding 105°C according to claim 1, characterized in that: The melt index of the polyarylene sulfide resin is greater than 200 g / 10 min.
5. The high voltage cable material capable of withstanding 105°C according to claim 1, characterized in that: The epoxy resin is selected to have an epoxy value of 0.1-0.6 eq / 100g.
6. The high voltage cable material capable of withstanding 105°C according to claim 1, characterized in that: The nano inorganic powder is selected from at least one of MgO, ZnO, Al2O3, and SiO2; the nano inorganic powder has a nano size range of 20-50nm.
7. The high voltage cable material capable of withstanding 105°C according to claim 1, characterized in that: The cross-linking agent is at least one of dicumyl peroxide and benzoyl peroxide; the auxiliary cross-linking agent is at least one of diallyl phthalate, triallyl cyanurate and 1,2-polybutadiene.
8. A method for preparing a high-voltage cable material capable of withstanding 105°C as claimed in any one of claims 1 to 7, characterized in that: The specific preparation method is as follows: (1) weighing nano-inorganic powder, epoxy resin, polyarylene sulfide resin, and styrene maleic anhydride copolymer according to a mass ratio of 100:20-30:20-25:0.2-0.3, adding the mixture into a closed grinder for grinding and modification, and obtaining modified nano-inorganic powder; (2) 85-90 parts of low-density polyethylene, 8-10 parts of modified nano-inorganic powder, 0.5-0.8 parts of maleic anhydride, 1.5-2.5 parts of cross-linking agent, 0.2-0.5 parts of auxiliary cross-linking agent and 0.3-0.5 parts of antioxidant are mixed by automatic weight loss weighing according to weight parts, dispersed and mixed at high speed for 30-60 minutes in a high-speed mixer, and then extruded through a twin-screw extruder with the screw temperature set to 110-120°C, hot-melt extruded into strips, conveyed by a chain conveyor belt, air-cooled and pelletized to obtain a high-voltage cable material that can withstand 105°C; the twin-screw extruder is a low aspect ratio co-rotating twin-screw extruder with a screw aspect ratio of 25 / 1-30 / 1.
9. A cable, characterized in that: The high-voltage cable material capable of withstanding 105° C. as claimed in any one of claims 1 to 7 is used as the insulating layer.
10. A method for preparing the cable according to claim 9, characterized in that: The inner shielding layer, the insulating layer and the outer shielding layer are sequentially extruded on the conductor core by three-layer co-extrusion; after the extrusion is completed, the cable core is cross-linked at a pressure of 1.0-1.2MPa and 280-320℃ through a high-temperature nitrogen pipeline for 8-10min to obtain a cable core; an alloy lead sheath is wrapped around the cable core, and a sheath is extruded to obtain a cable; wherein the three-layer co-extrusion extruder is an extruder for the inner shielding layer, the insulating layer and the outer shielding layer, and is equipped with 65 type, 150 type and 90 type in accordance with the extrusion volume. Type single screw extruder; the processing temperature for extrusion of inner and outer shielding layers is set at 100-110℃; the processing temperature for extrusion of insulation layer is set as follows: stage one: 90℃, stage two 100℃, stage three 105℃, stage four 105℃, stage five 110℃, stage six 110℃, stage seven 110℃, stage eight 115℃, stage nine 115℃, stage ten 118℃; the 150 type extruder for extruding insulation layer is equipped with vacuum exhaust port, and the vacuum degree is set to 0.06-0.08MPa.
Citation Information
Patent Citations
Special PPS (polyphenylene sulfide) plastic having good bonding property with epoxy adhesive and preparation method of PPS plastic
CN108084711A
Nano calcium carbonate modified polyphenylene sulfide-polycarbonate alloy material and preparation method thereof
CN117089202A
Insulation sheet and laminated structure
JP2009062436A
Insulating film, adhesive film and flat cable
WO2020189401A1